Gypsum plaster board as well as preparation method and application thereof
By using the composite technology of phosphogypsum clinker and polyimide nanofiber, the application of phosphogypsum in paper gypsum board is solved, and paper gypsum board with high mechanical strength and safety and environmental protection is achieved.
Patent Information
- Application Number
- CN202411995758.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to effectively utilize phosphogypsum because it contains a large amount of impurities, resulting in poor bonding properties and low mechanical strength, which limits its application in paper gypsum board.
Phosphogypsum clinker is used as the main raw material for the board core, and combined with polyimide nanofibers as reinforcement, the connection stability between phosphogypsum crystals is improved through specific proportions, thereby improving the mechanical strength of paper gypsum board.
It realizes the high mechanical strength, heat resistance and wear resistance of paper gypsum board, meets the performance requirements of GB/T 9775-2008 "Paper gypsum board", and does not contain carcinogenic glass fibers, which are safe and environmentally friendly.
Smart Images

Figure BDA0005224494680000051
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new building materials, and in particular relates to a gypsum board and a preparation method and application thereof. Background Art
[0002] Phosphogypsum is a byproduct of the wet process of producing phosphoric acid. It has become the largest solid waste in my country. Theoretically, for every ton of phosphoric acid (measured in P2O5) produced, 4 to 5.5 tons of phosphogypsum will be produced. The current stockpile of phosphogypsum in my country has exceeded 700 million tons, but the resource utilization rate is less than 40%, and the annual cost of phosphogypsum storage is as high as several million yuan. The reason for this situation, in addition to the fact that the production area of phosphogypsum is far away from the consumer market and the transportation radius is long, is mainly due to the large amount of harmful impurities contained in phosphogypsum, which makes it difficult to achieve large-scale high-value utilization.
[0003] As a typical green building material, gypsum board has the advantages of light weight, fire resistance, sound insulation, thermal insulation, easy processing, green environmental protection, and space saving. Therefore, it is widely used in various industrial buildings and civil buildings as interior wall materials and decorative materials. At present, the raw materials for the production of gypsum board are mainly desulfurized gypsum. Compared with desulfurized gypsum, phosphogypsum contains a large amount of impurities such as iron, magnesium, and aluminum due to process reasons. Phosphogypsum gypsum board usually exhibits poor bonding performance and low mechanical strength, which limits the application of phosphogypsum. Therefore, there are few reports on the application of phosphogypsum in gypsum board.
[0004] At present, the commonly used strength additive in the production process of paper-faced gypsum board is glass fiber. The main components of glass fiber are silicon dioxide, aluminum oxide, calcium oxide, boron oxide, magnesium oxide, sodium oxide, etc. It is a typical inorganic fiber material. According to the alkali content in the material, it can be divided into alkali-free glass fiber (sodium oxide 0% to 2%, alumina borosilicate glass), medium alkali glass fiber (sodium oxide 8% to 12%, soda-lime silicate glass with or without boron) and high alkali glass fiber (sodium oxide more than 13%, soda-lime silicate glass).
[0005] CN118420309A discloses a gypsum board and a preparation method thereof. The gypsum board comprises an A layer, a B layer and an A layer from top to bottom, wherein the raw materials of the A layer comprise the following components: 100 parts by weight of desulfurized gypsum clinker, 50-75 parts by weight of water, 0.02-0.1 parts by weight of glass fiber, 0.1-2 parts by weight of foaming agent, 0.05-0.5 parts by weight of retarder, 0.2-2 parts by weight of starch, and 0.01-0.5 parts by weight of water reducer; the raw materials of the B layer comprise the following components: 100 parts by weight of desulfurized gypsum clinker, 60-80 parts by weight of water, 0.5-5 parts by weight of silica aerogel particles, 10-30 parts by weight of reinforcing emulsion, 0.05-0.2 parts by weight of glass fiber, 0.2-1 parts by weight of retarder and 0.2-1 parts by weight of starch. This technical solution wraps silica aerogel particles in an emulsion to prepare a middle layer of gypsum slurry, and adds glass fiber and other components to the upper and lower layers of gypsum slurry to ensure the strength of the paper-faced gypsum board.
[0006] Although glass fiber has the advantages of high temperature resistance, non-combustibility, heat insulation, and sound insulation, it usually shows brittleness and poor wear resistance, and is very easy to break at the connection of gypsum crystals, losing the effect of improving the strength of paper-faced gypsum board. In addition, glass fiber is a Class II B carcinogen, which can cause some lesions in human skin, eyes, lungs, etc.
[0007] Therefore, it is necessary to develop a high-strength paper-faced gypsum board that does not contain glass fiber and uses phosphogypsum as the main raw material to solve the problem of recycling phosphogypsum. Summary of the invention
[0008] In view of the deficiencies in the prior art, the object of the present invention is to provide a paper-faced gypsum board and a preparation method and application thereof. The method of the paper-faced gypsum board is simple, the process cost is low, the mechanical strength is high, and it will not cause harm to the human body, and the phosphogypsum can be recycled.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a gypsum board, comprising a board core and a facing paper, wherein the raw materials for preparing the board core comprise the following components by weight: 100 parts of phosphogypsum clinker, 0.5-0.7 parts of polyimide nanofiber (for example, 0.52 parts, 0.54 parts, 0.56 parts, 0.58 parts, 0.60 parts, 0.62 parts, 0.64 parts, 0.66 parts or 0.68 parts, etc.), 0.1-0.5 parts of a binder (for example, 0.15 parts, 0.20 parts, 0.25 parts, 0.30 parts, 0.35 parts, 0.40 parts or 0.45 parts, etc.), 0.2-1 parts of a foaming agent (for example, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, etc.), and 0.1-0.5 parts of a foaming agent (for example, 0.20 parts, 0.25 parts, 0.30 parts, 0.35 parts, 0.40 parts or 0.45 parts, etc.). 8 parts or 0.9 parts, etc.), retarder 0.05-0.1 parts (for example, 0.55 parts, 0.60 parts, 0.65 parts, 0.70 parts, 0.75 parts, 0.80 parts, 0.85 parts, 0.90 parts or 0.95 parts, etc.), water reducer 0.1-0.3 parts (for example, 0.12 parts, 0.14 parts, 0.16 parts, 0.18 parts, 0.20 parts, 0.22 parts, 0.24 parts, 0.26 parts or 0.28 parts, etc.), stabilizer 0.1-0.7 parts (for example, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts or 0.6 parts, etc.) and water 60-80 parts (for example, 62 parts, 64 parts, 66 parts, 68 parts, 70 parts, 72 parts, 74 parts, 76 parts or 78 parts, etc.).
[0011] In the present invention, the gypsum board uses phosphogypsum clinker as the main raw material of the board core and polyimide nanofiber as a reinforcing agent, which can improve the connection stability between phosphogypsum crystals, thereby increasing the mechanical strength of the gypsum board and producing high-quality gypsum board. Polyimide is a high-molecular polymer containing repeating units of imide ring functional groups in the molecular chain. Polyimide nanofiber has excellent flexibility and tensile strength, good heat resistance and wear resistance, and polyimide nanofiber is an environmentally friendly polymer material, harmless to the human body and cheap. The use of polyimide nanofiber to replace traditional glass fiber greatly enhances the mechanical strength, heat resistance and wear resistance of the gypsum board, thereby improving the safety of the gypsum board. By compounding phosphogypsum clinker, polyimide nanofibers, binders, foaming agents, retarders, water reducers, stabilizers and water in specific proportions, the prepared gypsum board has high longitudinal and transverse breaking loads. It is expected that phosphogypsum can completely replace natural gypsum or desulfurized gypsum to prepare gypsum board, thereby accelerating the resource utilization of phosphogypsum.
[0012] Preferably, the phosphogypsum clinker is prepared by ball milling and calcining phosphogypsum raw material.
[0013] Preferably, the ball milling time is 1 to 2 h, for example, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h or 1.9 h.
[0014] Preferably, the calcination temperature is 140-170°C (e.g., 145°C, 150°C, 155°C, 160°C or 165°C, etc.), and the calcination time is 1-3h (e.g., 1.2h, 1.4h, 1.6h, 1.8h, 2.0h, 2.2h, 2.4h, 2.6h or 2.8h, etc.).
[0015] Preferably, the pH of the phosphogypsum raw material is 4-6, for example, 4.2, 4.4, 4.6, 4.8, 5.0, 5.2, 5.4, 5.6 or 5.8.
[0016] Preferably, the impurities contained in the phosphogypsum raw material include water-soluble phosphorus pentoxide, F - Or Na + Any one or a combination of at least two of the following.
[0017] Preferably, the water-soluble phosphorus pentoxide, F - and Na + The content exceeds the secondary index in GB / T23456-2018 "Phosphogypsum".
[0018] In the present invention, the polyimide nanofiber can be a conventional commercially available product, or can be prepared by any method well known in the art, for example, it can be prepared by the following preparation method: (i) condensing and polymerizing a diamine and a dianhydride in a reaction solvent to obtain a polyamic acid solution; (ii) spinning and thermally imidizing the polyamic acid solution obtained in step (i) to obtain a polyimide nanofiber membrane, and then crushing the polyimide nanofiber membrane into short fibers to obtain the polyimide nanofiber.
[0019] Preferably, the polyimide nanofibers include any one of BPDA-ODA type polyimide nanofibers, PMDA-ODA type polyimide nanofibers, BPDA-BPA type polyimide nanofibers or PMDA-BPA type polyimide nanofibers, or a combination of at least two of them.
[0020] In the present invention, the BPDA-ODA type polyimide nanofiber refers to a polyimide nanofiber prepared with BPDA and ODA as raw materials; the PMDA-ODA type polyimide nanofiber refers to a polyimide nanofiber prepared with PMDA and ODA as raw materials; the BPDA-BPA type polyimide nanofiber refers to a polyimide nanofiber prepared with BPDA and BPA as raw materials; the PMDA-BPA type polyimide nanofiber refers to a polyimide nanofiber prepared with PMDA and BPA as raw materials; the ODA has a structure as shown in the following formula I; the BPA has a structure as shown in the following formula II; the BPDA has a structure as shown in the following formula III; the BMDA has a structure as shown in the following formula IV.
[0021]
[0022] Preferably, the polyimide nanofiber has a diameter of 200 to 500 nm (e.g., 230 nm, 260 nm, 290 nm, 320 nm, 350 nm, 480 nm, 510 nm, 540 nm or 570 nm, etc.) and a length of 3 to 9 mm (e.g., 4 mm, 5 mm, 6 mm, 7 mm or 8 mm, etc.).
[0023] In the present invention, the diameter of the polyimide nanofiber is preferably 200-500nm, and the mechanical properties of the prepared gypsum board are good. If the diameter of the polyimide nanofiber is too large, the density of the gypsum board is small, and the viscosity and mechanical properties of the board core are reduced; if the diameter of the polyimide nanofiber is too small, the mechanical properties of the prepared gypsum board are less enhanced.
[0024] Preferably, the tensile modulus of the polyimide nanofiber is 1.5 to 2.5 GPa (e.g., 1.6 GPa, 1.7 GPa, 1.8 GPa, 1.9 GPa, 2.0 GPa, 2.1 GPa, 2.2 GPa, 2.3 GPa, 2.4 GPa, etc.).
[0025] Preferably, the binder comprises starch.
[0026] Preferably, the starch comprises any one of modified cassava starch, pregelatinized starch or modified corn starch, or a combination of at least two thereof.
[0027] Preferably, the foaming agent comprises a cationic surfactant and / or a nonionic surfactant.
[0028] Preferably, the cationic surfactant includes any one of sodium dodecyl sulfate, dodecyldimethylbenzyl ammonium chloride or hexadecyltrimethylammonium chloride, or a combination of at least two thereof.
[0029] Preferably, the nonionic surfactant includes any one of alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester or alkylphenol polyoxyethylene ether, or a combination of at least two thereof.
[0030] Preferably, the retarder comprises a protein retarder.
[0031] Optionally, the protein retarder includes any one of a collagen retarder, a gelatin retarder, a whey protein retarder, a mussel protein retarder or a myosin retarder, or a combination of at least two thereof.
[0032] Preferably, the water reducing agent comprises a polycarboxylic acid type water reducing agent.
[0033] Preferably, the polycarboxylic acid water reducer includes any one of polyester polycarboxylic acid water reducer, polyether polycarboxylic acid water reducer, amide / imide polycarboxylic acid water reducer or amphoteric polycarboxylic acid water reducer, or a combination of at least two thereof.
[0034] Preferably, the stabilizer comprises a phosphate-type stabilizer.
[0035] Preferably, the phosphate stabilizer includes any one of trimetaphosphate, tetrametaphosphate, hexametaphosphate, tripolyphosphate or tetrapolyphosphate, or a combination of at least two thereof.
[0036] In a second aspect, the present invention provides a method for preparing the gypsum board according to the first aspect, the preparation method comprising the following steps:
[0037] (1) mixing phosphogypsum clinker, polyimide nanofibers, a binder, a foaming agent, a retarder, a water reducer, a stabilizer and water to obtain a gypsum slurry;
[0038] (2) pouring the gypsum slurry obtained in step (1) onto the facing paper, solidifying and forming a wet board, and heating and drying to obtain the paper-faced gypsum board.
[0039] In the present invention, the preparation method of the paper-faced gypsum board is simple and has low process cost. The gypsum slurry is poured on the facing paper. During the solidification process, the gypsum slurry and the facing paper can be overlapped and adhered firmly, and then the gypsum board is obtained by heating and drying.
[0040] Preferably, the coagulation molding in step (2) is performed by placing the mixture at 20-30°C (for example, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C or 29°C, etc.) for 10-30 min (for example, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, 24 min, 26 min or 28 min, etc.).
[0041] Preferably, the heating and drying comprises heating and drying at 210-220°C (e.g., 211°C, 212°C, 213°C, 214°C, 215°C, 216°C, 217°C, 218°C or 219°C, etc.) for 30-40min (e.g., 31min, 32min, 33min, 34min, 35min, 36min, 37min, 38min or 39min, etc.), and then heating and drying at 110-130°C (e.g., 112°C, 114°C, 116°C, 118°C, 120°C, 122°C, 124°C, 126°C or 128°C, etc.) to constant weight.
[0042] In a third aspect, the present invention provides a use of the gypsum board as described in the first aspect in building materials.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] The present invention uses phosphogypsum clinker as the main raw material of the board core of the paper-faced gypsum board and polyimide nanofiber as a reinforcing agent, so as to improve the connection stability between phosphogypsum crystals, thereby increasing the mechanical strength of the paper-faced gypsum board and producing high-quality paper-faced gypsum board. The longitudinal breaking load of the paper-faced gypsum board is ≥360N, and the transverse breaking load is ≥190N. Preferably, the longitudinal breaking load of the paper-faced gypsum board is ≥400N, and the transverse breaking load is ≥200N, which can meet the performance requirements of GB / T 9775-2008 "Paper-faced Gypsum Board" (longitudinal breaking load ≥400N, transverse breaking load ≥160N). DETAILED DESCRIPTION
[0045] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0046] Some of the raw materials used in the following examples and comparative examples are as follows. Unless otherwise specified, they are all common commercially available products.
[0047] Phosphogypsum raw material, pH 4.9, water-soluble phosphorus pentoxide content 1100 mg / kg, F - The content is 400mg / kg, Na + The content is 300mg / kg, and it comes from Anhui Salt Fertilizer Co., Ltd.
[0048] BPDA-ODA type polyimide nanofiber A, with a diameter of 300 nm, a length of 5 mm, and a tensile modulus of 2.5 GPa, was obtained from Jiangxi Xiancai Nanofiber Technology Co., Ltd.;
[0049] BPDA-ODA type polyimide nanofiber B, with a diameter of 150 nm, a length of 2 mm, and a tensile modulus of 1 GPa, was obtained from Jiangxi Xiancai Nanofiber Technology Co., Ltd.;
[0050] BPDA-ODA type polyimide nanofiber C, with a diameter of 550 nm, a length of 15 mm, and a tensile modulus of 3 GPa, was obtained from Jiangxi Xiancai Nanofiber Technology Co., Ltd.;
[0051] PMDA-ODA type polyimide nanofiber, with a diameter of 370nm, a length of 3mm, and a tensile modulus of 1.9GPa, is from Jiangxi Xiancai Nanofiber Technology Co., Ltd.;
[0052] BPDA-BPA type polyimide nanofibers, with a diameter of 270 nm, a length of 7 mm, and a tensile modulus of 2.2 GPa, were obtained from Jiangxi Xiancai Nanofiber Technology Co., Ltd.;
[0053] PMDA-BPA type polyimide nanofiber, with a fiber diameter of 410nm, a length of 5mm, and a tensile modulus of 1.5GPa, is from Jiangxi Xiancai Nanofiber Technology Co., Ltd.;
[0054] Modified corn starch, brand name GF-A101, sourced from Nantong Gaofeng Biotechnology Co., Ltd.
[0055] Pregelatinized starch, brand name GF-K325, was sourced from Nantong Gaofeng Biotechnology Co., Ltd.
[0056] Modified cassava starch, brand DA94040-500g, sourced from Guangdong Wengjiang Chemical Reagent Co., Ltd.;
[0057] Sodium dodecyl sulfate, from Jinan Huanzheng Chemical Co., Ltd.;
[0058] Alkylphenol polyoxyethylene ether, brand TX-10, from Guangzhou Qixu Chemical Co., Ltd.;
[0059] The collagen retarder, brand name KH-GR802, comes from Wuhan Huaxuan High-tech Co., Ltd.;
[0060] Gelatin protein retarder, brand name ZJ-G18N, from Hubei Zhaojia Materials Co., Ltd.;
[0061] Amphoteric polycarboxylic acid water reducer, brand XDL201027, from Hebei Xindali New Building Materials Co., Ltd.;
[0062] Polyester type polycarboxylate water reducer, brand name -10, from Jiangsu Subote New Materials Co., Ltd.;
[0063] Sodium hexametaphosphate, Na6P6O 18 , from Suzhou Qiding Chemical Co., Ltd.;
[0064] Sodium tetrametaphosphate, Na4P4O 12 , comes from Suzhou Qiding Chemical Co., Ltd.
[0065] Example 1
[0066] The present embodiment provides a paper-faced gypsum board and a preparation method thereof, wherein the paper-faced gypsum board comprises a board core and a face paper, the thickness of the board core is 9 mm, the thickness of the face paper is 0.25 mm, and the raw materials for preparing the board core comprise the following components: 100 kg of phosphogypsum clinker, 0.7 kg of BPDA-ODA type polyimide nanofiber A, 0.4 kg of a binder (modified corn starch), 0.7 kg of a foaming agent (sodium dodecyl sulfate), 0.1 kg of a retarder (bone collagen retarder), 0.3 kg of a water reducer (amphoteric polycarboxylic acid water reducer), 0.6 kg of a stabilizer (sodium hexametaphosphate) and 80 kg of water;
[0067] The phosphogypsum clinker is prepared by ball-milling the phosphogypsum raw material for 1.5 hours and calcining it at 150° C. for 2 hours.
[0068] The preparation method of the gypsum board comprises the following steps:
[0069] (1) mixing phosphogypsum clinker, BPDA-ODA type polyimide nanofiber A, a binder, a foaming agent, a retarder, a water reducer, a stabilizer and water to obtain a gypsum slurry;
[0070] (2) pouring the gypsum slurry obtained in step (1) onto the facing paper, placing it at 25° C. for 30 minutes to solidify and form a wet board, drying it in a dryer at 210° C. for 40 minutes, and then drying it at 130° C. to constant weight, to obtain the paper-faced gypsum board.
[0071] Example 2
[0072] This embodiment provides a paper-faced gypsum board and a preparation method thereof. The only difference between this embodiment and Embodiment 1 is that the BPDA-ODA type polyimide nanofiber A is replaced with PMDA-ODA type polyimide nanofiber of the same mass, and other conditions are the same as those in Embodiment 1.
[0073] Example 3
[0074] This embodiment provides a paper-faced gypsum board and a preparation method thereof. The only difference between this embodiment and Embodiment 1 is that the BPDA-ODA type polyimide nanofiber A is replaced with BPDA-BPA type polyimide nanofiber of the same mass, and other conditions are the same as those in Embodiment 1.
[0075] Example 4
[0076] This embodiment provides a paper-faced gypsum board and a preparation method thereof. The only difference between this embodiment and embodiment 1 is that the BPDA-ODA type polyimide nanofiber A is replaced with PMDA-BPA type polyimide nanofiber of the same mass, and other conditions are the same as those in embodiment 1.
[0077] Example 5
[0078] This embodiment provides a paper-faced gypsum board and a preparation method thereof. The difference between this embodiment and embodiment 1 is that the mass of BPDA-ODA type polyimide nanofiber A is adjusted to 0.6 kg, and other conditions are the same as those in embodiment 1.
[0079] Example 6
[0080] This embodiment provides a paper-faced gypsum board and a preparation method thereof. The difference between this embodiment and embodiment 1 is that the mass of BPDA-ODA type polyimide nanofiber A is adjusted to 0.5 kg, and other conditions are the same as those in embodiment 1.
[0081] Example 7
[0082] This embodiment provides a paper-faced gypsum board and a preparation method thereof, which is different from Example 1 only in that the mass of the binder (modified corn starch) is adjusted to 0.1 kg, and other conditions are the same as those in Example 1.
[0083] Example 8
[0084] This embodiment provides a paper-faced gypsum board and a preparation method thereof, which is different from Example 1 only in that the mass of the binder (modified corn starch) is adjusted to 0.5 kg, and other conditions are the same as those in Example 1.
[0085] Example 9
[0086] This embodiment provides a paper-faced gypsum board and a preparation method thereof. The only difference between this embodiment and Embodiment 1 is that the BPDA-ODA type polyimide nanofiber A is replaced with BPDA-ODA type polyimide nanofiber B of the same mass, and other conditions are the same as those in Embodiment 1.
[0087] Example 10
[0088] This embodiment provides a paper-faced gypsum board and a preparation method thereof. The only difference between this embodiment and embodiment 1 is that the BPDA-ODA type polyimide nanofiber A is replaced with BPDA-ODA type polyimide nanofiber C of the same mass, and other conditions are the same as those in embodiment 1.
[0089] Embodiment 11
[0090] The present embodiment provides a paper-faced gypsum board and a preparation method thereof. The paper-faced gypsum board includes a board core and a facing paper. The thickness of the board core is 9 mm, the thickness of the facing paper is 0.25 mm, and the raw materials for preparing the board core include the following components: 100 kg of phosphogypsum clinker, 0.7 kg of BPDA-ODA type polyimide nanofiber A, 0.4 kg of binder (pregelatinized starch), 0.2 kg of foaming agent (hexadecyltrimethylammonium chloride), 0.05 kg of retarder (bone collagen retarder), 0.2 kg of water reducer (amphoteric polycarboxylic acid water reducer), 0.7 kg of stabilizer (sodium hexametaphosphate) and 60 kg of water.
[0091] The phosphogypsum clinker is prepared by ball-milling phosphogypsum raw material for 2 hours and calcining at 140° C. for 3 hours.
[0092] The preparation method of the gypsum board comprises the following steps:
[0093] (1) mixing phosphogypsum clinker, BPDA-ODA type polyimide nanofiber A, a binder, a foaming agent, a retarder, a water reducer, a stabilizer and water to obtain a gypsum slurry;
[0094] (2) pouring the gypsum slurry obtained in step (1) onto the facing paper, placing it at 25° C. for 20 minutes to solidify and form a wet board, drying it in a dryer at 220° C. for 30 minutes, and then drying it at 110° C. to constant weight to obtain the paper-faced gypsum board.
[0095] Example 12
[0096] The present embodiment provides a paper-faced gypsum board and a preparation method thereof, wherein the paper-faced gypsum board comprises a board core and a face paper, the thickness of the board core is 9 mm, the thickness of the face paper is 0.25 mm, and the raw materials for preparing the board core comprise the following components: 100 kg of phosphogypsum clinker, 0.7 kg of BPDA-ODA type polyimide nanofiber A, 0.4 kg of a binder (modified cassava starch), 1 kg of a foaming agent (alkylphenol polyoxyethylene ether), 0.1 kg of a retarder (gelatin protein retarder), 0.1 kg of a water reducer (polyester type polycarboxylic acid water reducer), 0.1 kg of a stabilizer (sodium tetrametaphosphate) and 70 kg of water;
[0097] The phosphogypsum clinker is prepared by ball-milling the phosphogypsum raw material for 1 hour and calcining it at 170° C. for 1 hour.
[0098] The preparation method of the gypsum board comprises the following steps:
[0099] (1) mixing phosphogypsum clinker, BPDA-ODA type polyimide nanofiber A, a binder, a foaming agent, a retarder, a water reducer, a stabilizer and water to obtain a gypsum slurry;
[0100] (2) pouring the gypsum slurry obtained in step (1) onto the facing paper, placing it at 25° C. for 10 minutes to solidify and form a wet board, drying it in a dryer at 215° C. for 35 minutes, and then drying it at 120° C. to constant weight, to obtain the paper-faced gypsum board.
[0101] Comparative Example 1
[0102] This comparative example provides a paper-faced gypsum board and a preparation method thereof, which is different from Example 1 only in that BPDA-ODA type polyimide nanofiber A is not added, and other conditions are the same as those in Example 1.
[0103] Comparative Example 2
[0104] This comparative example provides a paper-faced gypsum board and a preparation method thereof, which differs from Example 1 only in that the BPDA-ODA type polyimide nanofiber A is replaced with glass fiber of the same mass (diameter of 300nm, length of 5mm), and other conditions are the same as those in Example 1.
[0105] Comparative Example 3
[0106] This comparative example provides a paper-faced gypsum board and a preparation method thereof, which is different from Example 1 only in that the mass of BPDA-ODA type polyimide nanofiber A is adjusted to 0.4 kg, and other conditions are the same as those in Example 1.
[0107] Comparative Example 4
[0108] This comparative example provides a paper-faced gypsum board and a preparation method thereof, which is different from Example 1 only in that the mass of BPDA-ODA type polyimide nanofiber A is adjusted to 0.8 kg, and other conditions are the same as those in Example 1.
[0109] The gypsum boards provided in the above-mentioned Examples 1-12 and Comparative Examples 1-4 were subjected to longitudinal breaking load and longitudinal breaking load tests according to GB / T 9775-2008 "Gypsum Board". The test results are shown in Table 1 below.
[0110] Table 1
[0111] Longitudinal breaking load (N) Transverse fracture load (N) Example 1 455.7 237.4 Example 2 411.8 211.4 Example 3 430.4 212.9 Example 4 406.7 208.5 Example 5 432.5 220.9 Example 6 415.8 202.1 Example 7 410.6 216.6 Example 8 445.3 231.9 Example 9 360.7 194.5 Example 10 370.8 193.4 Embodiment 11 393.0 207.1 Example 12 380.1 199.2 Comparative Example 1 323.9 143.3 Comparative Example 2 395.5 161.4 Comparative Example 3 374.4 155.3 Comparative Example 4 389.3 170.6
[0112] It can be seen from the contents of Table 1 that the longitudinal breaking load of the gypsum board provided in Examples 1-12 is 360.7-455.7N, and the transverse breaking load is 193.4-237.4N.
[0113] Compared with Example 1, the fracture load of the gypsum board prepared in Examples 9 and 10 is smaller. It can be seen that the performance of the gypsum board prepared by the polyimide nanofibers with a diameter of 200-500 nm and a length of 3-9 mm is better.
[0114] Compared with Example 1, if polyimide nanofibers are not added (Comparative Example 1), the longitudinal and transverse breaking loads of the prepared gypsum board are both low, and cannot meet the performance requirements of GB / T9775-2008 "Gypsum Board".
[0115] Compared with Example 1, if the polyimide nanofiber is replaced with glass fiber (Comparative Example 2), the longitudinal and transverse breaking loads of the prepared gypsum board are lower, and the longitudinal breaking load cannot meet the performance requirements of GB / T 9775-2008 "Gypsum Board".
[0116] Compared with Example 1, if the weight fraction of the polyimide nanofiber is too low (Comparative Example 3), the longitudinal and transverse fracture loads of the prepared gypsum board are both low, and the longitudinal fracture load cannot meet the performance requirements of GB / T 9775-2008 "Gypsum Board". If the weight fraction of the polyimide nanofiber is too high (Comparative Example 4), the density and other properties of the gypsum board are affected, thereby reducing the fracture load of the gypsum board. It can be seen that the performance of the gypsum board prepared by the weight fraction of the polyimide nanofiber within a specific range is better.
[0117] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate a paper-faced gypsum board and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A gypsum board, characterized in that: The paper-faced gypsum board includes a board core and a facing paper. The raw materials for preparing the board core include the following components in parts by weight: 100 parts of phosphogypsum clinker, 0.5-0.7 parts of polyimide nanofibers, 0.1-0.5 parts of a binder, 0.2-1 parts of a foaming agent, 0.05-0.1 parts of a retarder, 0.1-0.3 parts of a water reducer, 0.1-0.7 parts of a stabilizer and 60-80 parts of water.
2. The gypsum board according to claim 1, characterized in that: The phosphogypsum clinker is prepared by ball milling and calcining the phosphogypsum raw material; Preferably, the ball milling time is 1 to 2 hours; Preferably, the calcination temperature is 140-170°C and the calcination time is 1-3h; Preferably, the pH of the phosphogypsum raw material is 4 to 6; Preferably, the impurities contained in the phosphogypsum raw material include water-soluble phosphorus pentoxide, F - Or Na + Any one or a combination of at least two of the following: Preferably, the water-soluble phosphorus pentoxide, F - and Na + The content exceeds the secondary index in GB / T 23456-2018 "Phosphogypsum".
3. The gypsum board according to claim 1 or 2, characterized in that: The polyimide nanofibers include any one of BPDA-ODA type polyimide nanofibers, PMDA-ODA type polyimide nanofibers, BPDA-BPA type polyimide nanofibers or PMDA-BPA type polyimide nanofibers, or a combination of at least two thereof; Preferably, the polyimide nanofiber has a diameter of 200 to 500 nm and a length of 3 to 9 mm; Preferably, the tensile modulus of the polyimide nanofiber is 1.5 to 2.5 GPa.
4. The gypsum board according to any one of claims 1 to 3, characterized in that: The binder includes starch; Preferably, the starch comprises any one of modified cassava starch, pregelatinized starch or modified corn starch, or a combination of at least two thereof.
5. The gypsum board according to any one of claims 1 to 4, characterized in that: The foaming agent includes a cationic surfactant and / or a nonionic surfactant; Preferably, the cationic surfactant includes any one or a combination of at least two of sodium dodecyl sulfate, dodecyl dimethyl benzyl ammonium chloride or hexadecyl trimethyl ammonium chloride; Preferably, the nonionic surfactant includes any one of alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester or alkylphenol polyoxyethylene ether, or a combination of at least two thereof.
6. The gypsum board according to any one of claims 1 to 5, characterized in that: The retarder includes a protein retarder; Optionally, the protein retarder includes any one of a collagen retarder, a gelatin retarder, a whey protein retarder, a mussel protein retarder or a myosin retarder, or a combination of at least two thereof.
7. The gypsum board according to any one of claims 1 to 6, characterized in that: The water reducer includes a polycarboxylic acid type water reducer; Preferably, the polycarboxylic acid water reducer includes any one or a combination of at least two of polyester polycarboxylic acid water reducer, polyether polycarboxylic acid water reducer, amide / imide polycarboxylic acid water reducer or amphoteric polycarboxylic acid water reducer; Preferably, the stabilizer comprises a phosphate stabilizer; Preferably, the phosphate stabilizer includes any one of trimetaphosphate, tetrametaphosphate, hexametaphosphate, tripolyphosphate or tetrapolyphosphate, or a combination of at least two thereof.
8. A method for preparing a gypsum board according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) mixing phosphogypsum clinker, polyimide nanofibers, a binder, a foaming agent, a retarder, a water reducing agent, a stabilizer and water to obtain a gypsum slurry; (2) pouring the gypsum slurry obtained in step (1) onto the facing paper, solidifying and forming a wet board, and heating and drying to obtain the paper-faced gypsum board.
9. The preparation method according to claim 8, characterized in that: The solidification molding in step (2) is performed by placing the mixture at 20 to 30° C. for 10 to 30 minutes for solidification molding; Preferably, the heating and drying comprises heating and drying at 210-220° C. for 30-40 min, and then heating and drying at 110-130° C. to constant weight.
10. Use of the gypsum board according to any one of claims 1 to 7 in building materials.